Carbon nanomaterials for energy storage devices - Zhipeng Wang; Melvin Gan Jet Hong (Springer, Cham, 2018)
In accordance to the fast technology development and rapid increment in world population, the demand on energy supply is getting stronger and higher. The advancement of nanotechnology has enables new cutting edge materials science and engineering to tackle the challenges. Various types of nanomaterials were fabricated in order to achieve higher performance and efficiency, where conventional or bulk materials meet their limitations, not only in the energy-related fields but numerous fields. In energy storage, particularly supercapacitor applications, carbon nanomaterials such as carbon nanotubes, graphene, and their derivatives have received much attention due to their remarkable structure, morphology, electrical, and mechanical properties that are essential for enhancing energy storage capabilities. This chapter provides introduction of electrochemical capacitors or supercapacitors; introduction of carbon nanomaterials, specifically carbon nanotubes and graphene, which is highly associated with supercapacitor electrode materials; discussion on influence factors that affect energy storage process; reviews on research and development of carbon nanomaterial-based supercapacitors; and future perspectives, opportunities, and challenges.